2009
DOI: 10.1016/j.comgeo.2008.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Bounds on the quality of the PCA bounding boxes

Abstract: ÈÖÖÒÔÔÐ ÓÑÔÓÒÒÒØ ÒÒÐÝ×××´ÈÈȵÒÒÐÝ×××´ÈÈȵ × ÓÑÑÓÒÐÝ Ù××× ØÓ ÓÑÔÙØØ ÓÙÒÒÒÒÒ ÓÜ ÓÓ ÔÓÓÒØ ××Ø Ò R d º ÌÌÌ ÔÓÔÙ¹ ÐÐÖÖØÝ ÓÓ ØØØ× ÙÖÖ×ØØ ÐÐÐ× Ò Ø× ×Ô¸×Ý×Ô¸×Ý ÑÔÐÐÑÑÒØØØØÓÒ ÒÒ Ò ØØØ Ø ØØØØ Ù×ÙÙÐÐݸÈÈÈÙ×ÙÙÐÐݸÈÈÈ ÓÙÒÒÒÒÒ ÓÜÜ× ÕÙÙØØ ÛÐÐ ÔÔÖÓÜÜÑÑØØ ØØØ ÑÑÒÒÑÙѹÚÓÐÙÑÑ ÓÙÒÒÒÒÒ ÓÜÜ׺ ËËÒ ØØØÖÖ ÖÖ ÜÜÑÔÐÐ× ÓÓ ×ÖÖØØ ÔÓÓÒØ× ××Ø× Ò ØØØ ÔÐÐÒÒ¸××ÓÛ¹ÔÐÐÒÒ¸××ÓÛ¹ ÒÒ ØØØØ ØØØ ÛÓÖ×Ø ×× ÖÖØØÓ ÓÓ ØØØ ÚÓÐÙÑÑ ÓÓ ØØØ ÈÈÈ ÓÙÒÒÒÒÒ ÓÜ ÒÒ ØØØ ÚÓÐÙÑÑ ÓÓ ØØØ ÑÑÒÒÑÙѹÚÓÐÙÑÑ ÓÙÒÒ¹ ÒÒ ÓÜ ØØÒÒ× ØÓ ÒÒÒÒØݸÛÒÒÒÒØÝ¸Û ÓÒ××××Ö ÈÈÈ ÓÙÒÒÒÒÒ ÓÜÜ× ÓÖ ÓÒØØÒÙÓ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…The following lower and upper bounds on the quality of the PCA bounding boxes were shown in (Dimitrov et al, 2007a) and (Dimitrov et al, 2007b). Theorem 2.1…”
Section: Continuous Pcamentioning
confidence: 99%
See 2 more Smart Citations
“…The following lower and upper bounds on the quality of the PCA bounding boxes were shown in (Dimitrov et al, 2007a) and (Dimitrov et al, 2007b). Theorem 2.1…”
Section: Continuous Pcamentioning
confidence: 99%
“…In (Dimitrov et al, 2007b), it was shown that λ d,i = ∞ for any d ≥ 4 and any 1 ≤ i < d − 1. This way, there remain only two interesting cases for a given d: the factor λ d,d−1 corresponding to the boundary of the convex hull, and the factor λ d,d corresponding to the full convex hull.…”
Section: Continuous Pcamentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 700 DA models, approximately 50 -60% were not acceptable because they presented small, loosely connected or poorly defined DA "domains." The selection of the DA model was done by first computing a tight boundary around each DA model using principal components analysis (28) and then removing the DA models that presented an increase in one of the bounding-box lengths of more than 2 to 5% from the average value. For each accepted DA model, dummy atoms were clustered in two groups (each group representing a single hexamer), and the center of each cluster was calculated from the mean of the DA coordinates that belong to the cluster.…”
Section: Methodsmentioning
confidence: 99%
“…The principal components of discrete point sets can be strongly influenced by point clusters (Dimitrov, Knauer, Kriegel & Rote (2009)). To avoid the influence of the distribution of the point set, often continuous sets, especially the convex hull of a point set is considered, which lead to so-called continuous PCA.…”
mentioning
confidence: 99%